The transformation of wine yeasts with glucanase, xylanase and pectinase genes for improved clarification and filterability of wine - Strauss, Marlene (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric) -- Stellenbosch University, 2003.